2016
DOI: 10.1253/circj.cj-16-0126
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Using the Cabrera Sequence for Diagnosing Acute Coronary Syndrome

Abstract: The 12-lead electrocardiogram (ECG) is the important, initial examination for diagnosing acute coronary syndrome (ACS). In the traditional 12-lead ECG display, the precordial leads are displayed in their anatomically contiguous order, which makes it easy to understand the positional relationships between the precordial leads and the heart, but the limb leads are not. The "Cabrera sequence" displays the limb leads in an anatomically contiguous manner, which facilitates understanding of the positional relations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Because the right inferior myocardium is mainly supplied by RCA blood, when the RCA is occluded, the spatial vector of the ST-segment will be directed, resulting in greater STE in lead III than in lead II. [ 35 ] STE in III > II and STD in aVL > I performed best in specificity, but it was not conclusive enough for the small number of studies (n = 4). Previous study reported ST depression occurred more frequently in aVL than in any other lead, so despite poor specificity of STD in aVL (0.41), it was still valuable due to a sensitive early electrocardiographic sign of acute WIMI.…”
Section: Discussionmentioning
confidence: 86%
“…Because the right inferior myocardium is mainly supplied by RCA blood, when the RCA is occluded, the spatial vector of the ST-segment will be directed, resulting in greater STE in lead III than in lead II. [ 35 ] STE in III > II and STD in aVL > I performed best in specificity, but it was not conclusive enough for the small number of studies (n = 4). Previous study reported ST depression occurred more frequently in aVL than in any other lead, so despite poor specificity of STD in aVL (0.41), it was still valuable due to a sensitive early electrocardiographic sign of acute WIMI.…”
Section: Discussionmentioning
confidence: 86%
“…ECG from a patient with proximal LAD occlusion. ST elevation in anterior leads in combination with ST elevation in aVR in the standard presentation ( a ) is a sign of proximal LAD occlusion [16, 37]. In the Cabrera sequence ( b ), ST elevation in aVR is displayed as ST depression in −aVR, which makes it easy to appreciate the ST -segment progression.…”
Section: Main Textmentioning
confidence: 99%
“…The use of aVR is considered to be important in the differential diagnosis between STEMI and takotsubo cardiomyopathy [36, 37]. Although ST elevation can be absent on admission ECGs in many cases of takotsubo cardiomyopathy, both the characteristics of the ST elevation, when present, and its time course are similar to those in acute myocardial infarction [36].…”
Section: Main Textmentioning
confidence: 99%
“…Acute coronary syndrome (ACS) is a medical emergency ( Kosuge and Kimura, 2016 ). The underlying mechanism of ACS is triggered by atheromatous plaque enlargement, instability, and rupture or erosion ( Amsterdam et al, 2014 ; Saremi, 2017 ).…”
Section: Introductionmentioning
confidence: 99%